Monastic rules of Shenute († 465) - Natalia Golovnina (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
This article analyses the form of Shenute’s monastic rules. They are not extant as a single book but were collected by B. Layton from all writings of this Coptic author. Consequently, the first question that rises if whether all the rules are cited as they were included in the statute of the monastery, or sometimes their form was determined by thelaws of the genre and by purposes of the text in which they were preserved. The secondproblem is related to quotations and their functions in Shenute’s rules. The Coptic apa continues in his texts the cenobitic tradition, at the origins of which stands St. Pachomius the Great, whose rules are notable for their simplicity and pithiness. Shenute’s rules are, by contrast, rhetorically elaborate. In particular, they contain quotations, allusionsand references to the Bible and to regulations of his predecessor, whom Shenute calls“our fathers”. Another important problem in the study of characteristic features of the rules of the White Monastery is the occurrence of quotations (both from the Bible and from Pachomius’ rules).